Governance Frameworks for Sustainable Artificial Intelligence in Digital Business Practices - Sunarya, Po Abas; Handra, Tessa; Syahyono, Syahyono; Al-Farouqi, Kamal Arif; Sihotang, Sondang Visiana (ADI Publisher, 2026)
The rapid advancement of digital technologies has accelerated organizational transformation across industries, compelling firms to adopt emerging innovations such as Artificial Intelligence (AI) and cloud computing to enhance operational efficiency, scalability, and data-driven decision-making. Despite their growing adoption, challenges related to security, governance, and sustainability often constrain the realization of their full strategic value. This study aims to investigate the integrated role of AI and cloud computing in supporting secure and sustainable digital transformation, particularly in relation to efficiency, governance, and sustainability outcomes aligned with the Sustainable Development Goals (SDGs). A qualitative research design based on a systematic literature review was employed to synthesize insights from prior studies on AI, cloud computing, and digital transformation. The findings indicate that cloud computing provides scalable and secure infrastructure, while AI enhances intelligent automation, predictive analytics, and decision-making capabilities. Furthermore, their integration generates synergistic effects that improve operational efficiency, strengthen data governance, and support sustainability through optimized resource utilization. These results highlight the complementary relationship between cloud computing and AI in enabling secure, efficient, and sus- tainable digital ecosystems. This study contributes to the digital transformation and governance literature by offering an integrated conceptual perspective and provides practical insights for organizations in aligning technological adoption with sustainability and governance objectives.